One Market, Two Rationalities: How Android and iOS Users Translate Quality into Satisfaction - Fendy Cuandra; Stefhani Susanto; Lilis Susilawaty; Sheila Septiany (Penerbit Goodwood, 2026)
Purpose: This study examines the effects of product quality and service quality on customer experience, customer trust, and customer satisfaction among Android and iOS smartphone users in Indonesia through the lens of rational choice theory.Research Methodology: A quantitative approach was employed using an online survey of 463 smartphone users (236 Android and 227 iOS) selected through purposive sampling. Data collected from 22 validated indicators were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Results: Product quality and service quality significantly influenced customer experience and customer trust across both platforms. However, customer satisfaction was formed through different evaluation patterns, with Android users emphasizing functionality and affordability, whereas iOS users prioritized ecosystem integration and brand credibility. The mediation effects of customer experience and customer trust also differed between the two user groups.Conclusions: Customer satisfaction is shaped by product quality, service quality, customer experience, and customer trust, with distinct mechanisms observed across smartphone ecosystems.Limitations: Findings may be constrained by the cross-sectional design, online self-reported data, and the predominance of younger respondents.Contributions: This study extends rational choice theory by explaining platform-specific customer evaluation mechanisms and provides practical insights for enhancing customer satisfaction in the smartphone industry.